Tactical Trend Trading Strategies for Surviving and Thriving in Turbulent Markets - Robbins, Robert; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
"Follow trends and make money, or don't follow trends and don't make money. Robert Robbins wants investors to follow trends. His effort is to be saluted." $1 (BMichael W. Covel, bestselling author of Trend Following, The Complete Turtle Trader, and Trend Commandments "A must-read for both the experienced and newcomers. The student has bypassed his mentor." $1 (BRalph Bloch, consultant at Bulls, Bears, & Bloch "Rob presents both the new and experienced trader with insights needed for successful trading. As a long-time trend follower, I share many of Rob's thoughts in Tactical Trend Trading. If you are truly interested in learning an investment strategy without the hype from a real trader, then this is the one definitive source." $1 (BAndrew Abraham, author of Learn How to Trend Follow Conventional wisdom has long insisted that the best$1 (Bif not the only$1 (Bstock market strategy worth employing is the traditional buy-and-hold model. But buy-and-hold investing is no match for today$1 (Bs turbulent markets, where real change happens every day and companies and entire industries are stamped out in the blink of an eye. Fortunately, there is a better way, one that enables market participants to preserve their capital while increasing their net gains in even the most volatile of markets. That way is trend trading, and with Tactical Trend Trading as your guide, you will be better prepared than ever before to tackle$1 (Band profit from$1 (Bevery curveball that today$1 (Bs topsy-turvy markets throw your way. Written by hedge fund manager and trend trader Robert Robbins, Tactical Trend Trading starts out from the basic premise that if market participants learn to embrace change, they will be better able to harness its ability to unlock profits in every corner of the markets. To that end, Robbins equips you not only with the technical trading tools you need to analyze the market backdrop and identify and trade with market-prevailing trends, but also psychological guidelines that will enable you to blast through the emotional obstacles that stand in the way of profit generation and risk control. Rich in detail yet easy to digest and implement, Tactical Trend Trading covers: The basics of trend trading, including what it is, its primary benefits and drawbacks, what type of commitment it entails, and how you can use it every day to profit from market volatility; How to leverage technical analysis and sentiment indicators to pinpoint profit-generating stocks, sectors, and trends, predict market corrections, and execute perfectly timed trades; Mental strategies for surmounting the ingrained psychological and emotional habits that prevent traders from realizing true financial success; Techniques for developing a systematic approach to the markets that will enable you to survive and thrive in up, down, and sideways markets; And much more. Along the path to becoming a successful trend trader, your technical acumen and mental fortitude will be tested every step of the way. Prepare yourself for the brave new world of today$1 (Bs ever-changing financial markets with Tactical Trend Trading, which provides you with all the moneymaking insights you need to capture trends, trade with the flow, and pull in profits, regardless of whether market conditions are good or bad.s
Keywords: Economics; Economics/Management Science; Business/Management Science, general